Repair of postpneumonectomy bronchopleural fistula using pedicled pericardial flap supported by fibrin glue - Jabłoński, Sławomir (Int Wound J, 2013)
Effective closure of the postpneumonectomy bronchopleural fistula (PBF) with the use of different techniques still remains a challenge for thoracic surgeons. The aim of this study was to evaluate the efficacy of modified method of PBF closure using pedicled pericardial flap (PPF) supported by fibrin glue (FG). The efficacy of the late PBF closure with the use of two surgical methods was compared. In 10 patients, the edges of the PBF were covered with FG and PPF. In the second group of nine patients, myoplasty was used to close the bronchial fistula. Postsurgical follow‐up was for 1 year. In the first group, the healing of the fistula was achieved in 100% of the cases, whereas in the second, myoplasty group, healing was achieved in only 66·67% of the cases. The number of complications was similar in both groups. Pericardial flap supported by fibrin glue can be an effective method adjunctive to the treatment of PBF in selected patients.